2017
DOI: 10.1177/0734242x17705726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curing time on selected properties of soil stabilized with fly ash, marble dust and waste sand for road sub-base materials

Abstract: The properties of sub-base filling materials in highway construction are essential, as they can determine the performance of the road in service. Normally, the existing materials are removed and replaced with new materials that have adequate load-bearing capacity. Rising environmental concern and new environmental legislations have made construction professionals consider other methods. These methods include stabilizing the existing materials with other additives to improve their performance. Additives can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
2
9
1
Order By: Relevance
“…Similarly, the decrease in MDD is significant for 1% to 9% addition of both lime and cement than 2% to 12% blending with MD and RHA separately, with MD marking the least reduction of all. However, reference [37] concluded that MDD of medium plasticity clay is expected to increase with the addition of fly ash, MD, and "waste sand"; the results obtained in the present study are somewhat deviating because of two main aspects. Firstly, for the RHA-clay blends, the compaction curves move diagonally downward to the right with an increase in RHA content, which leads to a decrease in MDD and an increase in the OMC.…”
Section: Compaction Characteristics Figurescontrasting
confidence: 71%
See 3 more Smart Citations
“…Similarly, the decrease in MDD is significant for 1% to 9% addition of both lime and cement than 2% to 12% blending with MD and RHA separately, with MD marking the least reduction of all. However, reference [37] concluded that MDD of medium plasticity clay is expected to increase with the addition of fly ash, MD, and "waste sand"; the results obtained in the present study are somewhat deviating because of two main aspects. Firstly, for the RHA-clay blends, the compaction curves move diagonally downward to the right with an increase in RHA content, which leads to a decrease in MDD and an increase in the OMC.…”
Section: Compaction Characteristics Figurescontrasting
confidence: 71%
“…Figure 3 suggests that cumulative passing percentage at equivalent grain size diameter of 0.002 mm is 45% and 40% for MD and RHA, respectively. e curing duration of 112 days was selected to study the long-term curing effect on strength characteristics of stabilized soils [37]. Upon completion of every curing period, the specimens were tested according to nomenclature presented in Table 3.…”
Section: Test Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of cementitious material by the reaction of lime with the pozzolans (Al 2 O 3 , SiO2, Fe 2 O 3 ) the presence of water is known as the hydration of FA. The hydrated calcium silicate gel or calcium aluminate gel can bind material together (Fırat et al, 2017). In the soil sample, no texture of the bond is seen (Figure 5e, f).…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 96%